TOPOLOGICAL INFLUENCE FROM DISTANT FIELDS ON TWO-DIMENSIONAL QUANTUM SYSTEMS - Konstantinos Moulopoulos (European Scientific Journal, ESJ, 2014)
A quantum system that lies nearby a magnetic or time-varying electric field region, and that is under periodic boundary conditions parallel to the interface, is shown to exhibit a hidden Aharonov-Bohm effect (magnetic or electric), caused by fluxes that are not enclosed by, but are merely neighboring to our system – its origin being the absence of magnetic monopoles in 3D space (with corresponding spacetime generalizations). Novel possibilities then arise, where a field-free system can be dramatically affected by manipulating fields in an adjacent or even distant land, provided that these nearby fluxes are not quantized (i.e. they are fractional or irrational parts of the flux quantum). Topological effects (such as Quantum Hall types of behaviors) can therefore be induced from outside our system (that is always fieldfree and can even reside in simply-connected space). Potential novel applications are outlined, and exotic consequences in solid state physics are pointed out (i.e. the violation of Bloch theorem in a field-free quantum periodic system), while formal analogies with certain high energy physics phenomena and with some rather unexplored areas in mechanics and thermodynamics are noted.